Empire and after : Englishness in postcolonial perspective - MacPhee, Graham, 1968-; Poddar, Prem (Berghahn Books, 2007)
The growing debate over British national identity, and the place of ""Englishness"" within it, raises crucial questions about multiculturalism, postimperial culture and identity, and the past and future histories of globalization. However, discussions of Englishness have too often been limited by insular conceptions of national literature, culture, and history, which serve to erase or marginalize the colonial and postcolonial locations in which British national identity has been articulated. This volume breaks new ground by drawing together a range of disciplinary approaches in order to res.